Effect of Eight-Week Transcranial Direct-Current Stimulation Combined with Lat Pull-Down Resistance Training on Improving Pull-Up Performance for Male College Students - Qian Li; Jiaqi Yan; Hanya Dai; Minjie Qiao; Mingxin Gong; Wenxin Niu; Ye Yang; Lejun Wang (Life)
The aim of this study was to investigate the effects and potential mechanisms of 8-week transcranial direct-current stimulation (tDCS) combined with resistance training (RT) on pull-up performance in male college students. Twenty-five male college students were randomly assigned to either RT combined with anodal tDCS stimulation (RT + tDCS) or RT alone (RT). Participants of both groups engaged in lat pull-down training programs for 8 weeks, with the RT + tDCS group receiving 20 min tDCS before each RT session. Pre- and post-intervention tests included pull-up endurance (number of repetitions), flexed arm circumference (FAC), and lat pull-down maximal voluntary isometric contraction (MVIC) peak force. During the pull-up endurance test, surface electromyography (sEMG) was recorded for the bicep brachii (BB), tricep brachii (TB), brachioradialis (BR), anterior deltoid (AD), middle deltoid (MD), posterior deltoid (PD), pectoralis major (PM), and latissimus dorsi (LD) muscles. Both groups demonstrated significant improvements in pull-up endurance and lat pull-down MVIC peak force after training, but no significant difference between the two groups was observed in the post-training test. Additionally, muscle activation of BR, PD, and PM decreased significantly in both groups, while the RT + tDCS group also demonstrated a significant reduction in TB coactivation after training. These findings suggest that eight weeks of tDCS combined with lat pull-down training and lat pull-down training alone can both significantly improve pull-up performance, which may be attributed to enhanced muscle contraction capacity. Although no significant training gains were found between the two training groups, the RT + tDCS group showed a significant decrease in TB coactivation and the enhancement of elbow flexion muscle contraction efficiency after training.